DAKWAH BERBASIS BUDAYA MELALUI UPACARA SEKATEN DI SOLO - Devi Pramudita, Octaviana (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2022)
da'wah mission has been passed down from generation to generation from the time of the prophets and apostles and then their companions to today's scholars and preachers. The law of da'wah is obligatory for a Muslim to others with several conditions and da'wah is mandatory for Muslims to each of them. The success of da'wah is part of the success in upholding the Islamic religion. The essence of da'wah is inviting people to the right path and straightening it to the path of Allah SWT, as in Qs. Al-Rum: 30. There are 3 methods of preaching, namely al-hikmah, al-mauidzah al-hasanah, and al-mujJadi. Da'wah which is currently being carried out uses cultural elements in it (contemporary). This study focuses on the analysis of cultural-based Da'wah at the Sekaten ceremony in Solo with a literature study research method analyzing data collection using references from books, documents, and relevant journals. The results obtained are that Sekaten is a ceremony commemorating the birthday of the Prophet Muhammad SAW, which initially started with the playing of Sunan Giri's gamelan (Kyai Guntumadu and Kyai Guntursari) in the Solo, then the presentation of several pieces created by the guardians, ending with Grebeg Maulud in the form of a procession mountains (prepared food) crops.